P48 Comparing bmi with skinfolds to estimate age at adiposity rebound and its associations with later cardio-metabolic risk markers. (2nd September 2017) - Gravio, C Di; Krishnaveni, GV; Somashekara, R; Veena, SR; Kumaran, K; Krishna, M; Karat, SC; Fall, CHD
Abstract : Background: Adiposity rebound (AR), defined as the lowest point before the second rise in body mass index (BMI), occurs between the ages of 5 and 7. Early age at AR is associated with higher risk of obesity in later life. However, BMI as a measure of adiposity has limitations: first, BMI incorporates both fat and lean mass, second, BMI is calculated from both height and weight. To identify the AR, a direct measure of fat (i.e. skinfold thickness) might be more relevant. We used data from the Mysore Parthenon Birth Cohort to compare relative merits of BMI and skinfolds in identifying AR and predicting BMI and cardio-metabolic risk factors at 13.5 years. Methods: The cohort was set up in 1997 in Mysore, India, to examine the long-term effects of gestational diabetes on cardiovascular disease risk factors in the offspring. Children were followed-up annually until 5 years, and 6-monthly after that for detailed anthropometry. At 13.5 years, 545 children had measurements of cardio-metabolic risk markers. We used non-linear splines and regression analyses (STATA version 14) to characterise the subject-specific growth of BMI and skinfolds (sum of triceps and subscapular skinfolds) throughout childhood, and to assess the associations between age at AR, BMI and cardio-metabolic risk factors. Results: BMI and skinfolds had similar trajectories with both reaching their minimum between 5 and 6 years. Average age at AR was similar between the two measures (5.94 years and 5.73 years respectively), with skinfold-derived AR being characterised by higher variability (standard deviation: 1.47 years and 2.18 years respectively). Later age of BMI-derived AR was associated with lower BMI (−0.89kg/m 2 ; 95% CI:[−1.04, –0.74kg/m 2 ]), fat mass (−1.14 kg; 95% CI:[−1.36, –0.91 kg]), HOMA-IR (−0.12; 95% CI:[−0.17, –0.07 kg]) and blood pressure (systolic BP:−0.78; 95% CI:[−1.26, –0.31 kg]; diastolic BP: −0.46; 95% CI:[−0.87, –0.04]) at 13.5 years. Similar results were obtained for skinfold-derived AR. Many of the above associations were fully explained by fat mass at 13.5 years. However, the association between skinfold-derived AR and SBP was still significant after adjusting for fat mass (−0.37; 95% CI:[−0.72, –0.01]). Conclusion: BMI and skinfolds produced similar estimates of age at adiposity rebound. Associations of AR with BMI and cardio-metabolic risk factors at 13.5 years were comparable regardless of how we derived AR. AR appears to be related to later cardio-metabolic risk markers through its association with fat mass. Skinfolds, as a more direct measure of adiposity than BMI, may be a better method for estimating AR when available.